2009
DOI: 10.1142/s0219749909004992
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Quantum Roulette

Abstract: In this paper, by using permutation matrices as a representation of symmetric group S N and Fourier matrix, we investigate quantum roulette with an arbitrary N -state. This strategy, which we introduce, is general method that allows us to solve quantum game for an arbitrary N -state. We consider the interaction between the system and its environment and study the effect of the depolarizing channel on this strategy. Finally, as an example we employ this strategy for quantum roulette with N = 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Salimi et al [6] used permutation matrices and the Fourier matrix as a representation of the symmetric group S n . They viewed quantum roulette as a typical n-state quantum system and developed a methodology that allowed them to solve this quantum game for arbitrary n. As an example, they employed their technique for a quantum roulette with n = 3.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Salimi et al [6] used permutation matrices and the Fourier matrix as a representation of the symmetric group S n . They viewed quantum roulette as a typical n-state quantum system and developed a methodology that allowed them to solve this quantum game for arbitrary n. As an example, they employed their technique for a quantum roulette with n = 3.…”
Section: Related Workmentioning
confidence: 99%
“…This means that our games take place in the two-dimensional complex Hilbert space H 2 and we shall not be concerned with higher dimensional analogs of the PQ game like those in [6,7].…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
See 1 more Smart Citation
“…where σ i are the Pauli matrices. The Kraus operators for a single qutrit depolarizing noise are given as [28]…”
Section: Qubit-qutrit System In Depolarizing Noisementioning
confidence: 99%
“…A study of quantum walks on simple lattice is well known in physics(see [14]). Recent studies of quantum walks on more general graphs were described in [8,7,10,13,15,16,17,18,19,20,21,22]. Some of these works studies the problem in the important context of algorithmic problems on graphs and had suggested that quantum walks is a promising algorithmic technique for designing future quantum algorithms.…”
Section: Introductionmentioning
confidence: 99%